2001
DOI: 10.1210/jcem.86.11.8041
|View full text |Cite
|
Sign up to set email alerts
|

Height Velocity and Skeletal Maturation in Elite Female Rhythmic Gymnasts

Abstract: Rhythmic gymnasts performing under conditions of high intensity are exposed to particularly high levels of psychological stress and intense physical training, factors that can contribute to the observed delay in skeletal maturation and pubertal development, and alter optimal growth. The study was conducted in the field, during the International, European, and World Rhythmic Sports Gymnastics Championships of the years 1997-2000, and included 104 elite female rhythmic gymnasts, aged 12-23 yr. The study included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
8

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 21 publications
3
38
0
8
Order By: Relevance
“…Bone age delay in both males and females was more pronounced in the latter. We and others have previously shown that the development of puberty in rhythmic gymnasts follows the bone age rather than the chronological age (9,19,21). Low body weight and low body fat reflect an energy deficit, evident in AG, as a consequence of intensive physical training (high energy output) and low caloric diet (low energy input).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Bone age delay in both males and females was more pronounced in the latter. We and others have previously shown that the development of puberty in rhythmic gymnasts follows the bone age rather than the chronological age (9,19,21). Low body weight and low body fat reflect an energy deficit, evident in AG, as a consequence of intensive physical training (high energy output) and low caloric diet (low energy input).…”
Section: Discussionmentioning
confidence: 92%
“…The protocol is presented in detail elsewhere (9). Briefly, it included noninvasive clinical and laboratory determinations as well as the completion of a questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…By studying female elite rhythmic gymnasts (n ¼ 104, age 12-23 years, mean sports training 32 h/ week), Georgopoulos's group [12] demonstrated that adult height was not significantly different from predicted height estimated at first evaluation and was significantly higher than target height ( Figure 1). In addition, the examined gymnasts continued to increase in height up to the age of 18 years, when final adult height has already been reached in normal growing girls [6].…”
Section: Sports Activity and Growthmentioning
confidence: 97%
“…Eliakim and co-workers [15] followed a group of adolescent males involved in Figure 1. Target height and adult height in female elite rhythmic gymnasts (a; drawn from data reported in [12]) and female elite artistic gymnasts (b; drawn from data reported in [14]); while the former subjects reached their genetic target height, the latter subjects did not (see text). (Data represent mean +1 SD.)…”
Section: Sports Activity and Growthmentioning
confidence: 99%
“…Women who exercise and maintain normal menstrual cycles appear to have higher bone mineral density than amenorrheic women, and low bone mineral density has been reported for adult athletes with amenorrhea (Arasheben et al, 2011). Delayed menarche, menstrual irregularities, and low body fat are frequently seen in aesthetic athletes (Georgopoulos et al, 2001) but, contrary to the commonly held belief that the low body fat is principally responsible for the menstrual dysfunction, it appears that low energy availability is the primary cause (Loucks, 2003). According to Loucks (2003), dysfunction of reproductive hormones occurs below 20-30 kcal/ kg lean body mass/day of energy availability (energy consumed minus exercise energy expended in training).…”
Section: Relative Energy Deficiency In Sport Disordered Eating and mentioning
confidence: 99%